THE EFFECT OF ESTROGEN DEFICIENCY ON THE FUNCTIONING OF ARC CENTRAL LINK SEGMENTAL REFLEX - Tkachenko, S.S.; Rodynskyi, O.H.; Horb-Havrylchenko, I.V. (World of Medicine and Biology, 2021)
The purpose of this study was to analyze the influence of the spinal cord interneuronal pool due to the lack of estrogens on the functioning of the central link of the reflex arc. The study was performed on 51 mature rats (females). Estrogen deficiency was induced by ovariohysterectomy. L5 dorsal root was stimulated by single and paired square-wave impulses. The response was recorded on the dorsal surface of the spinal cord and the ventral root at the same level. The overall effect of estrogen deficiency is an increase in the excitability of spinal cord motor neurons, activity of the interneuronal pool, inhibition of nerve transmission at low frequencies due to inhibitory influense of the gelatin substance neurons. First time in vivo results of a study of the modulating effect of the interneuron pool on the motoneuron apparatus of the spinal cord in acute hypoestrogenemia will help to understand the pathophysiological mechanisms of impaired sensitivity, motor activity and seizures that are part of menopausal syndrome, especially in ovarian disease.
Keywords: menopause; estrogen; spinal cord; interneuron; motoneuron